2015
DOI: 10.1155/2015/421253
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Secretome of Clinically Relevant Preparations of Adipose-Derived Mesenchymal Stem Cells Cocultured with Hyaluronan

Abstract: Osteoarthritis (OA) can be a debilitating degenerative disease and is the most common form of arthritic disease. There is a general consensus that current nonsurgical therapies are insufficient for younger OA sufferers who are not candidates for knee arthroplasties. Adipose-derived mesenchymal stem cells (MSCs) therapy for the treatment of OA can slow disease progression and lead to neocartilage formation. The mechanism of action is secretion driven. Current clinical preparations from adipose tissue for the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
1
12
0
4
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) decreased with increasing concentration of HA and significantly for the 2 mg/mL concentration. This was consistent with our previous investigations of HA and MSC coculture [ 29 ]. VEGF may play an active role in the pathogenesis of OA.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Vascular endothelial growth factor (VEGF) decreased with increasing concentration of HA and significantly for the 2 mg/mL concentration. This was consistent with our previous investigations of HA and MSC coculture [ 29 ]. VEGF may play an active role in the pathogenesis of OA.…”
Section: Discussionsupporting
confidence: 94%
“…MIF is considered to be a proinflammatory mediator especially in OA and acts in local tissue to increase neutrophil and macrophage migration to regions of inflammation. Our previous investigations also showed increased secretion of MIF by MSCs cultured with HA [ 29 ]. Vascular endothelial growth factor (VEGF) decreased with increasing concentration of HA and significantly for the 2 mg/mL concentration.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have reported many growth factors and cytokines derived from the CM of various stem cells [19][20][21][85][86][87][88][89], which could be responsible for the paracrine protective effects of stem cells against several diseases. Consequently, the use of stem cells CM instead of direct implantation of stem cells may be a feasible approach to overcome the limitations of current cell-based therapy.…”
Section: Secretome As a Therapeutic Strategy: Conditioned Mediamentioning
confidence: 99%
“…MSC niche interactions appear to be of mutual benefit since MSC release a wide range of bioactive factors that confer trophic and immune-modulatory effects, such as cytokines and distinct forms of miRNA and tRNA species (Hsiao et al, 2012 ; Baglio et al, 2015 ). More and more reports have unraveled the potent features of the MSC secretome, which now is thought to become by itself a regenerative therapeutical tool (Sdrimas and Kourembanas, 2014 ; Gallina et al, 2015 ; Succar et al, 2015 ; Tran and Damaser, 2015 ).…”
Section: Moving Into Clinicsmentioning
confidence: 99%